Serum human trophoblast cell surface antigen and T-box protein 5 levels play a role in predicting adverse pregnancy outcomes in eclampsia: Trop-2 and TBX5 in predicting adverse pregnancy outcomes in eclampsia - Li, Yao; Huang, Sutong; Xuan, Yan; Shen, Hao; Zhang, Weiwei; Li, Jia (Journal of Medical Biochemistry, 2025)
Objective: The levels of human trophoblast surface antigen (Trop-2) and T-box protein 5 (TBX5) in the serum of patients with preeclampsia were detected, and their value in predicting adverse pregnancy outcomes was analyzed.Methods: A total of 196 pregnant women with preeclampsia who underwent prenatal examinations and delivered in our hospital from October 2021 to September 2024, as well as 196 healthy pregnant women, were selected as the eclampsia group and the control group, respectively. The 196 pregnant women with preeclampsia were divided into two groups according to their pregnancy outcome: the adverse outcome group and the good outcome group. Using the enzyme-linked immunosorbent assay (ELISA), the levels of serum Trop-2 and TBX5 were measured. Using multivariate logistic regression analysis, the factors impacting the various pregnancy outcomes of preeclamptic pregnant women were examined.Results: Compared with control group, the serum TBX5 levels in the eclampsia group (20.86±6.45 µg/L vs. 15.34±5.07 µg/L), as well as diastolic blood pressure, FBG, 24-hour urine protein, TG, systolic blood pressure and TC, were significantly greater. The levels of Trop-2 [(5.46±1.72) µg/L vs. (7.37±2.08) µg/L]. The total incidences of preterm infants, fetal distress, placental abruption and adverse pregnancy outcomes in the eclampsia group were significantly greater than those in the control group (P
Keywords: Serum human trophoblast cell surface antigen; T-box protein 5; Adverse pregnancy; Eclampsia